1966
DOI: 10.1172/jci105332
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic response of the mucosa of human small intestine to x-ray exposure.

Abstract: Prolonged and repeated exposure to sublethal doses of total body irradiation induce significant morphologic changes in the mucosa of the small intestine of laboratory animals. These changes include decreased mitosis in the intestinal crypts, necrosis of crypt epithelial cells, and decreased height of crypts and villi (2-5).In man, submucosal fibrosis (6, 7) and mucosal and submucosal lymphangiectasia (8) have been noted together with gastrointestinal malabsorption

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(42 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…Inflammatory infiltrate in the lamina propria is one of the important acute radiation injuries in the rectum (30). In the present study, it was ameliorated with amifostine, and intrarectal administration further rendered it at the control level.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Inflammatory infiltrate in the lamina propria is one of the important acute radiation injuries in the rectum (30). In the present study, it was ameliorated with amifostine, and intrarectal administration further rendered it at the control level.…”
Section: Discussionsupporting
confidence: 55%
“…It is possible that reduced epithelial barrier function allows access of antigens to subepithelial tissues, which induce a reactive eosinophilic inflammatory reaction (20). Trier et al (30) also defined this homogeneous eosinophilic material in the submucosal tissue, as suggestive of edema fluid, in a pioneer prospective study. We showed that the increase of eosinophil leucocytes in the lamina propria was prevented only by intrarectal administration of amifostine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we are unaware of published data dealing with the possible decrease of biliary excretion in leukaemic animals, hepatic dysfunction has been extensively reported in tumour-bearing animals (Greenstein, 1954;Homburger, 1957). It is also well known that factors that reduce the rate of cell renewal in the small intestine of animals, like starvation and protein depletion (Hooper & Blair, 1958;Takano, 1964;Deo & Ramalingaswami, 1965), cause a shortening of villi and absorptive surface is significantly reduced (Clark & Harland, 1963;Trier & Browning, 1966). Finally, any modification in the state of the epithelial membranes could modify the rate of drug absorption in the gut; given the extensive changes in the biochemistry of cancerous animals (Greenstein, 1954), it would not be surprising that the dynamics of the membranes of columnar epithelical cell be altered and drug absorption impaired.…”
Section: Jmentioning
confidence: 99%
“…Symptoms such as nausea, anorexia, weight loss and diarrhoea may be sufficiently severe to delay completion of the planned treatment and compromise the possibility of cure (1 -3). It has generally been considered that acute radiation enteritis represents a mucosal disease of limited duration (4) and the potential contribution of motor dysfunctions to diarrhoea and other symptoms of radiation enteritis has received little attention. Recent studies in humans have shown that following radiotherapy the rate of small intestinal transit is increased and may contribute to small intestinal malabsorption (5,6).…”
mentioning
confidence: 99%